Effect of aspirin on pruritus. Issue 6552 (11th October 1986) - Daly, B M; Shuster, S
Abstract : The effect of 900 mg aspirin on persistent itch from chronic dermatoses other than urticaria (eight patients) and other causes (five patients) was measured subjectively using a 10 cm line and objectively as nocturnal scratch using limb meters. There was no change in itch or scratch and it is concluded that aspirin neither affects itch centrally by a pain related mechanism nor affects itch physiologically by cyclo-oxygenase inhibition in the skin.